DAMPAK PEMEKARAN DESA TERHADAP PENGELOLAAN POTENSI DAERAH DI DESA BUNTU BUANGIN - Wijaya, Adil; Adnan, Andi Astinah; Sundari, Sundari (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2024)
Adil Wijaya, 2023. The Impact of Village Expansion on Regional Potential Management in Buntu Buangin Village, Pitu Riase District, Sidenreng Rappang Regency, (supervised by Mrs. Andi Astinah Adnan and Mr. Akhyaruddin Hakim) This study aims to determine the impact of village expansion on regional potential management in Buntu Buangin Village. This research uses quantitative methods. Respondents were selected using an incidental sampling technique with 70 respondents as a data source. Data collection techniques used were observation, questionnaires/questions, and literature study with data processing and analysis techniques using SPSS 21 for window. The results showed that the impact of village expansion on the management of physical potential in the village of Buntu Buagin, Pitu Riase District, Sidenreng Rappang Regency had a percentage of 84% in the very good category. So that indicators of physical potential can be categorized as